Approaches to language, culture, and cognition : the intersection of cognitive linguistics and linguistic anthropology - Yamaguchi, Masataka, 1968-; Tay, Dennis, 1981-; Blount, Ben G., 1940- (Palgrave Macmillan, 2014)
"The study of language, culture, and cognition has become increasingly fragmented into separate disciplines and paradigms. This volume aims to re-establish dialogue between cognitive linguists and linguistic anthropologists with 11 original papers on language, culture and cognition, and an editorial introduction. It demonstrates that cognitively-informed perspectives can contribute to a better understanding of social, cultural, and historical phenomena, and argues that cognitive theories are relevant to linguistic anthropology. "-- Resumé vydavatele